2004
DOI: 10.1007/s00436-003-1038-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crude extracts of Mucuna pruriens (Fabaceae) and Carica papaya (Caricaceae) against the protozoan fish parasite Ichthyophthirius multifiliis

Abstract: The ciliate Ichthyophthirius multifiliis is among the most pathogenic parasites of fish maintained in captivity. In the present study, the effects of the crude methanolic extract of leaves of Mucuna pruriens and the petroleum-ether extract of seeds of Carica papaya against I. multifiliis were investigated under in vivo and in vitro conditions. Goldfish (Carassius auratus auratus) infected with the parasites were immersed for 72 h in baths with M. pruriens extract, and for 96 h in baths with C. papaya extract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 29 publications
4
65
0
3
Order By: Relevance
“…In the treatment of 19.2 mg/L potassium ferrate(VI), the lethal effects of the potassium ferrate(VI) were found after 30 min, and at 4 h, approximately 80% of the tomonts were dead. The timeresponse relationship was also found in the study of Ekanem et al (2004). They reported the effects of crude extracts of Mucuna pruriens and Carica papaya against I. multifiliis and confirmed this relationship.…”
Section: Discussionsupporting
confidence: 55%
“…In the treatment of 19.2 mg/L potassium ferrate(VI), the lethal effects of the potassium ferrate(VI) were found after 30 min, and at 4 h, approximately 80% of the tomonts were dead. The timeresponse relationship was also found in the study of Ekanem et al (2004). They reported the effects of crude extracts of Mucuna pruriens and Carica papaya against I. multifiliis and confirmed this relationship.…”
Section: Discussionsupporting
confidence: 55%
“…Buchmann et al (2003) reported raw extracts from garlic (Allium sativum) were used to treat I. multifiliis infestation by killing theronts and tomonts. Ekanem et al (2004) accessed the effects of crude extracts from Mucuna pruriens and Carica papaya against I. multifiliis. Green tea extract has been reported to kill Ichthyobodo necator (Suzuki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an efficacious therapeutant is needed that is not potentially hazardous to human health as a residue in muscle tissue. Several studies have evaluated alternatives to malachite green for treatment of the disease (Wahli et al 1993, Straus & Griffin 2001, Ekanem et al 2004, Heinecke & Buchmann 2009, Straus & Meinelt 2009, and the compounds that proved effective against free-swimming stages of the parasite could therefore be suitable as bath treatments. However, treatment of ichthyophthiriasis via bath application is difficult because the therapeutant eliminates neither the trophonts located in the epidermis of the fish nor the encysted tomonts, both of which are less susceptible to chemical treatment than the theronts (Mei nelt et al 2009).…”
Section: Introductionmentioning
confidence: 99%